Completeness of exercise reporting among randomized controlled trials on pelvic floor muscle training for women with pelvic organ prolapse: A systematic review. Issue 6 (31st May 2021) - Giagio, Silvia; Innocenti, Tiziano; Salvioli, Stefano; Lami, Alessandra; Meriggiola, Maria Cristina; Pillastrini, Paolo; Gava, Giulia
Abstract: Aims: This systematic review aimed to assess the completeness of exercise reporting in randomized controlled trials (RCTs) on pelvic floor muscle training (PFMT) for women with pelvic organ prolapse (POP). Methods: MEDLINE, Cochrane Central, CINHAL, Embase, SCOPUS, and PEDro databases were searched up to October 2020. Full‐text RCTs comparing PFMT to any type of intervention among women with any type and stage of POP were eligible for inclusion. Completeness of intervention was evaluated with t20he template for intervention description and replication (TIDieR) and the consensus on exercise reporting template (CERT). Inter‐rater agreement for each item of the tools was calculated. Results: Twenty‐six RCTs were included. None of the studies completely reported all intervention descriptors. On average 57.1% (6.8 ± 2.4; out of 12) of the overall TIDieR items and 35.3% (6.7 ± 2.9; out of 19) of the CERT were well described. In particular, 7 and 5 items were completely reported more than 50% of the time for the TIDieR and CERT, respectively. Frequent shortcomings were the undetailed reporting of information regarding tailoring and modifications of exercises and their adherence. Detailed descriptions of exercise repetitions to enable replication were missing in 53.8%. According to the CERT, only 11.5% of the RCTs sufficiently described the main providers' characteristics. Conclusion: The completeness of PFMT reporting for women with POP is still below desirable standards and it is insufficient to ensure transferability into practice. The present results may add relevant knowledge and contribute to improving adequate reporting of exercise.